2017
DOI: 10.1002/cjoc.201600637
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of FeS2 Quantum‐Dots/Functionalized Graphene‐Sheet Composites as Advanced Anode Material for Sodium‐ion Batteries

Abstract: FeS2 quantum‐dots/functionalized graphene‐sheet (QDs/FGS) composites are prepared by a facile and scalable method. The FeS2 QDs/FGS composites can be used as anode materials for sodium‐ion batteries. The FeS2 QDs/FGS composites can achieve large specific discharge and charge capacities of 742 and 683 mAh•g−1 (based on the total mass of the FeS2 QDs/FGS composites) at the current density of 0.5 A•g−1 in the first cycle, respectively, and retain a reversible charge capacity of 552 mAh•g−1 after 100 cycles. The F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…The peak at 0.5 V is the reduction peak of FeS 2 ,,. And most striking, the CV curve is still in its original form in the subsequent 300 cycles although the three small peaks disappeared due to decomposition reactions of Fe 2 O 3 and FeS 2 nanoparticles ,. This results demonstrates the surprising cycling stability, in keeping with the results of Figure d.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The peak at 0.5 V is the reduction peak of FeS 2 ,,. And most striking, the CV curve is still in its original form in the subsequent 300 cycles although the three small peaks disappeared due to decomposition reactions of Fe 2 O 3 and FeS 2 nanoparticles ,. This results demonstrates the surprising cycling stability, in keeping with the results of Figure d.…”
Section: Resultssupporting
confidence: 80%
“…To develop high performance anode materials for SIBs, Fe‐based materials, such as FeNb 11 O 29 , Fe 2 O 3 , Fe 3 O 4 , FeS 2 , and FeS, and Fe 1‐x S, have been extensively studied because of their high theoretical capacities, low cost, earth‐abundance and nontoxicity. Among them, Fe 2 O 3 and FeS 2 have been considered as promising candidates for SIBs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous efforts to improve the electrochemical characteristics of FeS 2 have mainly focused on designing nanostructured composites with bifunctional carbon‐based materials that offer high conductivity and serve as a structure‐reinforcing buffer matrix against significant volume variation upon cycling. [ 21,22 ] For example, Chen et al demonstrated that an FeS 2 /carbon nanotube neural network exhibited enhanced cycling stability with a reversible capacity of 394 mAh g –1 after 400 cycles at 200 mA g –1 . [ 14 ] Yin et al prepared FeS 2 @porous octahedral carbon derived from a metal‐organic framework, which showed an excellent rate capability of up to 5000 mA g –1 and good cycle performance.…”
Section: Introductionmentioning
confidence: 99%